Perception of Teachers on Leadership Attributes and Administrative Effectiveness of Secondary Schools Principals in Nasarawa State, Nigeria. - Ogieva, Adesuwa Evelyn (International Journal of Educational Management, 2021)
The study investigated the perception of teachers on leadership attributes and the administrative effectiveness of secondary schools principals in Nasarawa State, Nigeria. The study was designed to establish the administrative effectiveness of secondary schools principals based on gender and proprietorship. Descriptive survey research design was employed for the study. The population of the study comprised all the teachers 23,905 in the 683 secondary schools in Nasarawa State. The sample of 300 respondents (teachers) was selected from both public and private secondary school through the simple random sampling technique. The instrument used for data collection was titled Questionnaires on Secondary School Principal Administrative Effectiveness (QSSPAE) which was administered on teachers in order to establish their perception on the principals' administrative effectiveness. The instrument was found reliable at 0.60 and the logical validity of 0.70 was established. Hypotheses were tested using the t- test statistic at 0.05 level of significance. The findings revealed that the proprietorship has no significant influence on the administrative effectiveness of secondary school principals. It also confirmed that there is a significant difference in the administrative effectiveness of male and female secondary school principals. Hence, it was concluded that principals in the private secondary schools are as effective as their counterparts in the public secondary schools while male principals were found to be more effective administratively than their female counterparts in the secondary schools in Nasarawa State. Recommendations were made based on the findings among which include; the female secondary school principals should be given top priority in trainings on administrative effectiveness, government, individuals and all stakeholders in education should encourage principals in both public and private schools through the provision of adequate welfare packages to boost their morals,secondary school principals in both public and private should be given adequate orientation and training on administrative effectiveness, the female principals in